Non-communicable disease risk factors and Covid-19 antibody levels after vaccination - Wea, Brigitta Yuliana; Hananta, Linawati; Astiarani, Yunisa (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Non-communicable diseases (NCDs) have been identified as predictors of the severity of Coronavirus Disease 2019 (Covid-19). Some factors like smoking, alcohol consumption, and physical inactivity, which are associated with NCDs, may potentially hinder the efficacy of vaccines, reducing their ability to prevent the severity and complications of infectious diseases such as the Covid-19. Objective: This study investigated the NCD, risk factors associated with the levels of quantitative antibodies after the second Covid-19 vaccination.Methods: A cross-sectional study was conducted at a Covid-19 vaccination centre in Jakarta. Ninety subjects, aged ≥18, completed demographic and NCDs risk factor questionnaires. Blood samples were collected and analysed by using the electro chemiluminescence immunoassay analyser (ECLIA) method to measure quantitative antibody levels 30 days after 2nd Covid-19 vaccination. The bivariate analysis was performed to explore associations among the variables. The logistic regression was subsequently performed to identify the factors that remained independent in influencing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody status. Results: The mean value of antibody level in this study was 191 U/ml. The results indicated that 35.5% (n=32) of respondents had SARS-CoV-2 antibody levels below average. The regression results suggested that the odds of having higher antibody levels were reduced for individuals with hypertension (Adjusted Odd Ratio [AOR] = 0.74, p value = 0.022), diabetes (AOR = 0.82, p value = 0.038) comorbidities accompanied with smoking (AOR = 0.55, p value = 0.044), drinking alcohol (AOR = 0.92, p value = 0.030), and low physical activity levels (AOR = 0.67, p value = 0.043). Conclusion: The study found that 35.5% of participants had SARS-CoV-2 antibody levels below the average. Factors such as hypertension, diabetes, comorbidities with smoking, alcohol consumption, and low physical activity were associated with reduced odds of higher antibody levels.